CLASS ACTION RESEARCH: THE EFFECT OF INTENSIVE READING IN TEACHING READING COMPREHENSION - Mustakim Hadi; Siti Wahyu Puji Anggraini; Moh Gufron; M. Mizanul Haq (Berugak Baca, 2024)
The objective of this research is to know is there any effect of intensive reading in teaching reading comprehension (Class Action Research study of MA Nurul Wahyi NW Mujur). This study investigates the effect of intensive reading in teaching reading comprehension. The writer will intentionally emerge the phenomena. Considering the experts’ opinions above, it can be determined that this study is categorized as the class action research study. The population (subject) of this study was all of the second year students of MA Nurul Wahyi NW Mujur in the school year 2023/2024 which consist of 15 students. The data that are needed in this data in this study is the result of pre and post-test. Pre-test was given to the subject before doing teaching-learning process by using intensive reading. While, post test was given after applied the intensive reading, in the teaching-learning. The items of pre and post-test are the same. Based on the data gained for Class Action Research group in pre-test gained the lowest and the highest score 10 and 60. While, in the post-test obtained the lowest and highest score 80 and 100. For the control group in the pre-test gained the lowest and highest score 10 and 60. While, the in the post-test the lowest and highest score were 80 and 100. The effect of intensive reading in teaching reading comprehension Class Action Research study at MA Nurul Wahyi NW Mujur). In the school year 2023/2024 has differences before and after applied intensive reading. It can be seen from the result of data analysis which is indicated that the diagram of the means score was 91.250 for experimental group was 28.6 and the mean score of control group. The deviation scores for experimental group was 28,6 and control group was 6.083.3. While It’s means that after treatment by using intensive reading there was a positively significant in teaching reading comprehension.